2016
DOI: 10.5114/pg.2015.52495
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics of children with early clinical manifestation of inflammatory bowel disease

Abstract: IntroductionInflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC), is a chronic condition of the colon and small intestine. The disease is common in young people (children and young adults), but it is rare in children younger than five years of age. Therefore, IBD developing during the first years of life (under the age of 5) is known as an early-onset IBD (EO-IBD), and it is considered to be a specific entity with a distinct phenotype. However, the available data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Our study found that those with EO‐CD had lower height and weight percentiles than patients with LO‐CD at the time of diagnosis and at each follow‐up visit. In prior studies, the most common complication of IBD was anemia . In our study, patients with EO‐CD also had lower levels of hemoglobin, albumin, zinc and rion at diagnosis than those with LO‐CD.…”
Section: Discussionsupporting
confidence: 63%
“…Our study found that those with EO‐CD had lower height and weight percentiles than patients with LO‐CD at the time of diagnosis and at each follow‐up visit. In prior studies, the most common complication of IBD was anemia . In our study, patients with EO‐CD also had lower levels of hemoglobin, albumin, zinc and rion at diagnosis than those with LO‐CD.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have reported that VEO‐IBD cases have more colonic and perianal involvement, especially in pediatric Crohn's disease 3,6–9 . In this study, all but one patient underwent colonoscopy.…”
Section: Discussionmentioning
confidence: 79%
“…Younger IBD patients, especially those with VEO‐IBD, are known to carry higher genetic components in their disease etiology 8,9,12,13 . A genetic diagnosis is particularly important because some monogenic IBD cases have been reported as curable by hematopoietic stem cell transplantation 2,14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental factors and genetic predisposition may also play a role in I-IBD. 2 The presence of specific mutations affecting the interleukin-10 (IL-10) receptor and Mediterranean fever (MEFV) gene seems to play a fundamental role in I-IBD. 3,4 Previous reports described the response of I-IBD patients with familial Mediterranean fever (FMF) to colchicine therapy.…”
mentioning
confidence: 99%